2016
DOI: 10.1021/acs.jproteome.5b01111
|View full text |Cite
|
Sign up to set email alerts
|

A Urinary Metabolic Signature for Multiple Sclerosis and Neuromyelitis Optica

Abstract: Urine is a metabolite-rich biofluid that reflects the body's effort to maintain chemical and osmotic homeostasis. Clinical diagnosis routinely relies on urine samples because the collection process is easy and noninvasive. Despite these advantages, urine is an under-investigated source of biomarkers for multiple sclerosis (MS). Nuclear magnetic resonance spectroscopy (NMR) has become a common approach for analyzing urinary metabolites for disease diagnosis and biomarker discovery. For illustration of the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 45 publications
(90 reference statements)
2
42
0
1
Order By: Relevance
“…Metabolomics can provide information on the in vivo mechanism of action and to eliminate compounds likely to cause problems with side effects [43]. Recent studies have utilized metabolomics to search for biomarkers for colon cancer [44] and multiple sclerosis [45]. …”
Section: Applications Of Metabolomicsmentioning
confidence: 99%
“…Metabolomics can provide information on the in vivo mechanism of action and to eliminate compounds likely to cause problems with side effects [43]. Recent studies have utilized metabolomics to search for biomarkers for colon cancer [44] and multiple sclerosis [45]. …”
Section: Applications Of Metabolomicsmentioning
confidence: 99%
“…The activation of T cells and the accumulation of mononuclear phagocytes can promote destruction of the myelin sheath, ultimately leading to the formation of focal demyelinated lesions in MS (Lassmann, Bruck, & Lucchinetti, 2007). The alteration of energy metabolism is discovered in urine from MS patients (Gebregiworgis et al, 2016). Glycolysis intermediates lactate has the potential differentiating between healthy controls and MS patients.…”
Section: Warburg Effect Aggravates the Process Of Multiple Sclerosismentioning
confidence: 99%
“…In this process, tyrosine is considered as an intermediate involved in the tricarboxylic acid cycle, as well as a metabolic regulator participating in the formation of ketone bodies. Teklab Gebregiworgis investigated glycolysis and ketone body synthesis and decomposition as vital metabolic pathways in NMOSD and multiple sclerosis (Gebregiworgis et al, ). Other research has shown that the brain comsumes a quarter of the whole body's glucose supply to sustain brain functioning, and when the blood gludcose supply fails to meet brain energy needs, the ketone body can alternatively serve as an energy source (Mathur, Lopez‐Rodas, Casanova, & Marti, ).…”
Section: Resultsmentioning
confidence: 99%
“…It was confirmed that the production of AQP-4 antibody accelerated the intracellular glutamate transport (Saikali, Cayrol, & Vincent, 2009) into ketone bodies (Marcos et al, 2016). In this process, tyrosine is in NMOSD and multiple sclerosis (Gebregiworgis et al, 2016). Other research has shown that the brain comsumes a quarter of the whole body's glucose supply to sustain brain functioning, and when the blood gludcose supply fails to meet brain energy needs, the ketone body can alternatively serve as an energy source (Mathur, Lopez-Rodas, Casanova, & Marti, 2014).…”
Section: Biomarker Identification and Pathogenesis Predictionmentioning
confidence: 89%